Carbon fixation genes in biomining microorganisms - Zammit, Carla; Mutch, Lesley; Watling, H; Watkin, Elizabeth (Nature Publishing Group, 2008)
Background and aims: Studying metabolic pathways will help provide a better understanding of the role of different microorganisms within biomining environments. The majority of microorganisms involved in biomining are autotrophs which rely on atmospheric carbon fixation for growth. The aim of this study is to investigate genes involved with carbon fixation in a range of biomining microorganisms.